A Language Appraisal on Kompas.Com News Through Interpersonal Meaning - Widyaiswara, Tiara; Nurman, Moh.; Fatmawaty, Riryn; Falakhah, Eva Nurul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research analyzes three news items on the Kompas.com site related to the installation of Puan Maharani's billboards installed around the Mount Semeru evacuation using the Appraisal Theory. Appraisal theory is relate about an interpersonal system in linguistics that focuses on negotiating social relations about one's assessment of something. This study used qualitative documentation as research design. For data collection techniques used reading and searching for news techniques, selecting research data news according to the formulation of the problem and research objectives, then conducting a language analysis of news taken from Kompas.com using appraisal which focus on attitude. Then the data are processed to be able to classify appraisal attitude according to the category. So the writer found as many as eight data including the appraisal attitude of the affect category found there were two data. As for appraisal attitude in the judgment category, six data were found. So from the three news reports, a negative assessment was found from the public because they discussed morality and the normality of Puan's billboards at Mount Semeru refuge. Those many thought that Puan wanted to increase her popularity and electability for the 2024 general election by taking advantage of the disaster situation. Keywords: Appraisal, Attitude, Puan Maharani Billboards